(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
On the basis of modern sozological concepts the creation principles of ecological network in a Steppe zone of Ukraine and criteria of selection of its structural elements have been developed. The regional plan of the Steppe zone’s ecological network which includes 3 key territories of international, 24 – of national, 38 – of regional level and also 4 ecocorridors of international, 4 of national and 21 – of regional level have been developed and characterized.